The effect of inlet swirl on knock limits in spark ignition engines - Allison, Colin Bidden (Department of Mechanical Engineering, 2016)
An investigation was undertaken to determine the effect of swirl ratio on knock limits in spark ignition engines. Initially it was attempted to find a correlation between swirl ratio and Knock Limited Spark Advance (KLSA) for a selection of commercially available engines. A comparison of measured swirl ratios and KLSA indicated that no such correlation could be found. This was put down to the fact that other factors such as combustion chamber shape and spark plug location play a more dominant role in affecting knock limits than swirl level. Following from this, a single engine with a relatively poor swirl ratio was selected and the swirl level was altered. A novel method of increasing and decreasing the swirl level, with the same pressure drop in each case was developed, and this development is described. This method made it possible to perform dynamometer tests, measuring the KLSA timing for the cases of low and high swirl, while keeping all other parameters such as pressure, temperature, spark plug location and combustion chamber shape constant. All these factors are known to have an effect on the occurrence of knock. In this manner it was possible to determine whether swirl alone has any effect on knock limits. It was found that the high swirl case exhibited higher values of knock limited spark advance above the low swirl case although there was no significant change in torque. A comparison of rubber castings of the inlet ports of numerous engines was made, and is presented in a photographic form. This was done in order to assess how inlet port geometry affects swirl ratios. It was found that a helically shaped inlet port produced the greatest swirl ratio, non directed ports have average values and multiple inlet valve ports have very low swirl ratios. Furthermore, a comparison of swirl ratios of an inlet port with and without deposits, demonstrates that deposits have a significant effect on swirl ratios and volumetric efficiency. However, although the volumetric efficiency was reduced, the deposits enhanced the swirl ratios for this particular case. This is contrary to the general belief that deposits reduce swirl.